APLIKASI PENCATATAN LAPORAN PENJUALAN KITA-KITA.NET BERBASIS WEB - Victor Marudut Siregar; Heru Sugara; Gabriel Andrian Purba (Politeknik Bisnis Indonesia, 2019)
This study aims to design and implement an application for recording web-based sales reports at Kita-Kita.Net using the prototype method. By using the prototype method, the design and implementation of applications can be faster and according to what the client / user application wants. Recording of sales reports at Kita-Kita.Net which still manually makes recording errors often occur, due to these errors also have an effect on work efficiency at Kita-Kita.Net. By designing this application can minimize errors that occur in recording sales reports, as well as improve work efficiency, both time efficiency and energy efficiency at Kita-Kita.Net.